Aprender a pensar em História: um estudo com alunos do 6º ano de escolaridade - Isabel Barca; Marília Gago (Universidade do Minho, 2001)
The study explores the levels of arguments given by sixth graders when reasoning upon contradicting primary sources related with a specific historical issue. A sample of 83 sixth graders filled in a questionnaire asking for a crossinterpretation of four primary sources conveying different perspectives. The school where the study was carried out is located near the city of Braga. Through a qualitative analysis, four conceptual levels of argumentation (profiles) were traced: from a less elaborate profile of fragmented responses, with an intermediate level displaying a global understanding of messages towards two more sophisticated profiles suggesting an emerging opinion and decentration. The approximate equivalence of response distribution by profile suggests that students can use diversified historical sources in the "History and Geography of Portugal" class.